Analysis of the suitability and carrying capacity of coral reef ecotourism for diving tourism on Karampuang Island, Mamuju District, West Sulawesi Province - Arwin Arwin; Fanella Muhammad Askin Putra; Jalil Machfud Hapitah (Politeknik Negeri Sambas, 2025)
Nature tourism is a visit to a tourist spot that is still relatively natural, so it is minimal due to disturbance or pollution. The research objective was to analyze the cover condition, damage status of coral reefs, reef fish species diversity, and carrying capacity of the area for diving tourism development in the Karampuang Island Waters. The research was conducted from August 07 to October 07, 2020, in Karampuang Island, Mamuju Regency, West Sulawesi Province. The land suitability analysis used in the research was guided by the formula and matrix of land suitability for diving tourism and analysis of the area's carrying capacity. Based on the calculation of the research results, live coral cover, with an average of 27.26%, was included in the medium category. With a reef fish diversity index found at four stations ranging from 2.97-3.16, with 12 families, 33 species, and 557 individual fish, Karampuang Island is suitable for the development of diving tourism; the entire research area qualifies as marine tourism, especially diving tourism groups with suitability categories between 88.89-100% and the area reaches 52,740 m2 so that it can accommodate as many as 113 tourists per day.